Pteridophytes Diversity and Distribution Along The Elevational Gradient of Mount Penanggungan's Hiking Trail, East Java, Indonesia - Hasyim, Muhammad Asmuni; Hanifa, Berry Fakhry; Septiadi, Luhur; Firdaus, Firman; Setya, Yudha; Mulyono, Rizki Mujahidin; Achmad, Caesar Rasendria; Haq, Mochammad Nur Izzul (Jurnal Biodjati, 2023)
Pteridophytes (ferns) are a fundamental element of tropical rainforests, which provide excellent microhabitats for their development. In addition, the sensitivity of pteridophytes to shifts in microclimate and anthropogenic disturbances makes them excellent environmental bioindicators. The purpose of this study was to determine the diversity and distribution of pteridophytes along the elevational gradient of two well-known hiking trails of Mount Penanggungan, East Java, Indonesia. Using a 10x10 m2 plot and transect line, we examined the composition, species diversity using Shannon-Wiener diversity index (H'), relative abundance, and distribution pattern using Morisita index of dispersion (Id) of ferns along an elevational gradient (700–1500 m above sea level) on the hiking trails of Mount Penanggungan, i.e., Tamiajeng and Kunjorowesi. As many as 14 species from 7 families living in both terrestrial and arboreal types were identified. Species composition along the elevation gradient revealed a pattern of predominating species. The Shannon-Wiener diversity index (H') indicated a moderate level of diversity, where many pteridophytes species are found on the altitude gradient between (700-900 m dpl), and the Morisita index of dispersion (Id) indicated a clustered distribution pattern for most of the species. This pattern of diversity and distribution can be explained by changes in biotic and abiotic factors.